Prophet at the Bedside: A Model for Hospital Chaplaincy - Hatgas, Jonathan (Lumen et Vita, 2016)
In The Prophetic Imagination, Walter Brueggemann describes the role of the prophet as one who will “nurture, nourish, and evoke a consciousness and perception alternative to the consciousness and perception to the dominant culture around us.” Engaging in this understanding, I will raise the image of prophet as a model for hospital chaplains. Because of the complex reality of hospital chaplaincy, I will focus on working with families of patients “actively dying” a foreseeable death. The primary marks of the prophet are to be a disruptive force, to guide people toward a communal identity, to act as mediators between God and the people, and to orient the community toward the promised land or renewed covenant with God. Moses exemplifies these characteristics and concretizes them in the Exodus story, providing chaplains with an exemplar to aspire to. The Exodus story also offers a resonant narrative for families with elderly members in the hospital. There are many possible emotional connection points throughout. Families, like the Israelites, are groups of people held together by common ancestors and a common history. Both groups had triumphs and struggles. Maybe putting their loved one in the hospital seemed like an escape from the bondage of home care, but now they find themselves in the desert, aimless with faith faltering, and hope of a promise waning. They find themselves wary and doubtful. Prophetic chaplains can challenge the U.S. culture of invincibility and disposability while leading families through “the desert”, giving them a glimpse of the promised land, and ideally opening a space for them to strengthen in a shared identity.